Individual agency and social support in healing from conflict-related sexual violence: A case history from eastern DRC - Ali Bitenga Alexandre (Taylor & Francis Group, 2024)
ABSTRACTExamining the experience of a male survivor of rape through the salutogenic model and ecological theory, this case study explores how he moved towards the direction of health after an atrocious experience of sexual violence perpetrated by members of an armed group. The study illustrates how he was able to deploy agency by undertaking a number of health-promoting actions to recover from the physical, mental, and social effects of conflict-related sexual violence. Initiatives in the process of improving one's health include self-care practice, searching for specialised care when self-care seems inefficient, relocation to new a setting post-rape, starting a business, testing one's reproductive capacities, marrying, taking care of the way he dressed, learning a new language, developing public speaking skills, owning a piece of land, having regular medical check-ups and ascending to power and decision-making bodies. His narrative shows how these initiatives are mirrored by both opportunities and setbacks. While more traditional survey-based studies focus on identifying which practices might be helpful in a healing context, this study sheds light on how an individual healing process might be complex and nuanced and is an important starting point towards our efforts to theorise resilience for male survivors.